2020
DOI: 10.1101/2020.08.31.272583
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trunk sensory and motor cortex is preferentially integrated with hindlimb sensory information that supports trunk stabilization

Abstract: Sensorimotor integration in the trunk system has been poorly studied despite its importance for examining functional recovery after neurological injury or disease. Here, we mapped the relationship between thoracic dorsal root ganglia and trunk sensory cortex (S1) to create a detailed map of the extent and internal organization of trunk primary sensory cortex, and trunk primary motor cortex (M1) and showed that both cortices are somatotopically complex structures that are larger than previously described. Surpr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 116 publications
(160 reference statements)
0
1
0
Order By: Relevance
“…The ability of postural control is positively associated with the cortical activity. Previous studies showed that the primary motor cortex (M1), supplementary motor area (SMA), primary somatosensory cortex (S1), and dorsolateral prefrontal cortex (DLPFC) are involved in postural control (Teo et al, 2018;Solis-Escalante et al, 2019;Coelho et al, 2021;Nandakumar et al, 2021). Tsao et al (2008) found that the activation onset of TrA during single rapid arm flexion was related to the location and the map volume of M1 in the CLBP participants.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of postural control is positively associated with the cortical activity. Previous studies showed that the primary motor cortex (M1), supplementary motor area (SMA), primary somatosensory cortex (S1), and dorsolateral prefrontal cortex (DLPFC) are involved in postural control (Teo et al, 2018;Solis-Escalante et al, 2019;Coelho et al, 2021;Nandakumar et al, 2021). Tsao et al (2008) found that the activation onset of TrA during single rapid arm flexion was related to the location and the map volume of M1 in the CLBP participants.…”
Section: Introductionmentioning
confidence: 99%